Opportunities for meaningful inclusion: experience of individuals with intellectual and developmental disabilities with research - Dudley, Ally; Baker, Tai; Hardesty, Canyon; Moody, Eric J. (Frontiers in Pediatrics, 2025)
BackgroundIndividuals with intellectual and developmental disabilities (IDD) face numerous health disparities, particularly in rural communities. However, they are rarely included in the research process to address these challenges as co-researchers. Little is known about the experience of how individuals with disabilities participate as co-researchers, or the barriers they face.ObjectiveThe current study explores the experiences of individuals with IDD as co-researchers through discussions with individuals with IDD themselves, those who support them, and disability researchers.MethodData were collected through focus groups with individuals with IDD, individuals who support those with IDD, and disability researchers. Each group was asked about their journey through the research process, from beginning to end. Data were analyzed thematically by two independent coders.ResultsWhile all groups viewed the inclusion of individuals with disabilities as co-researchers as valuable, many barriers still prevented this population from fully participating in the research process. Individuals with IDD viewed research positively, especially when the topics were personally relevant. However, many thought research was intimidating and wanted additional support. Support providers expressed that the people they support have lots to contribute to research and felt empowered when participating. Disability researchers discussed many barriers to include individuals with IDD as co-researchers, including limited time, resources, and inflexibility of research processes. Researchers felt they could use more experience working with individuals with disabilities as co-researchers to integrate these individuals into all aspects of the process.DiscussionThere is broad interest in including those with IDD as co-research, but many barriers remain. Full inclusion can be supported by developing a welcoming and accessible environment. Researchers may need institutional support and training to pursue inclusive IDD research. Asking individuals with IDD for their expertise, develop topics of research that those with IDD can relate to, and involving support providers may be helpful. Developing innovative strategies to support inclusion is needed from all groups.